2005
DOI: 10.1080/11250000509356677
|View full text |Cite
|
Sign up to set email alerts
|

Functional responses and scope for growth of two non‐indigenous bivalve species in the Sacca di Goro (northern Adriatic Sea, Italy)

Abstract: A comparative study was carried out on the functional feeding behaviour of the infaunal Manila clam, Ruditapes philippinarum, and the epifaunal Asian date mussel, Musculista senhousia, inhabiting the Sacca di Goro lagoon, in response to changing temperature and variable quantity of food. The rates of clearance, ingestion, absorption, respiration, and energy budget (scope for growth, SFG) were measured and compared. The two non-indigenous species show a similar trend for all parameters measured in the two seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…At each time point, four randomly chosen clams from each tank (two controls and two treatments) were taken for physiological measurements. Measurement methods are fully described in Sgro et al (2005a), and followed the procedures outlined by Widdows and Staff (1997). Briefly, clearance rate was measured in plastic beakers (2 l) of filtered (0.45 lm) seawater, with two clams per beaker plus one control (without clams).…”
Section: Physiological Measurementsmentioning
confidence: 99%
“…At each time point, four randomly chosen clams from each tank (two controls and two treatments) were taken for physiological measurements. Measurement methods are fully described in Sgro et al (2005a), and followed the procedures outlined by Widdows and Staff (1997). Briefly, clearance rate was measured in plastic beakers (2 l) of filtered (0.45 lm) seawater, with two clams per beaker plus one control (without clams).…”
Section: Physiological Measurementsmentioning
confidence: 99%
“…Large mats of A. senhousia can indeed suffocate the hosting substrate, isolating the benthos from the overlying water column (Yamamuro et al, 2010). Moreover, A. senhousia, being an efficient suspension feeder (Sgrò et al, 2005), can severely reduce the food available for native suspension feeder bivalves, hence possibly promoting interspecific competition for resources (Crooks, 2001). On the other hand, byssal mats created by A. senhousia act as novel structures that can enhance habitat heterogeneity, offering shelter for different benthic organisms (Mistri, 2003(Mistri, , 2004aMistri et al, 2004;Munari, 2008;Katsanevakis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is, feeding behaviour in tuatua and cockles could have alternated seasonally. Sgro et al (2005) found feeding in two species of marine bivalve was affected negatively in some seasons when there were; low abundances of food in the water column, low qualities of food or high turbidity. Fluctuations seen in reaction time over seasons in the current study could be related to food availability and feeding behaviour or a combination of these factors.…”
Section: Behavioural Responsesmentioning
confidence: 97%